Piperine Impedes Biofilm Formation and Hyphal Morphogenesis of Candida albicans - Priya, Arumugam; Pandian, Shunmugiah Karutha (Frontiers in Microbiology, 2020)
Candida albicans is the primary etiological agent associated with the pathogenesis of candidiasis. Unrestricted growth of C. albicans in the oral cavity may lead to oral candidiasis which can progress to systemic infections in worst scenario. Biofilm of C. albicans encompasses yeast and hyphal forms, where hyphal formation and yeast to hyphal morphological transitions are contemplated as the key virulence elements. Current clinical repercussions necessitate the identification of therapeutic agent which can limit the biofilm formation and escalating the susceptibility of C. albicans to immune system and conventional antifungals. In the present study, a plant-derived alkaloid molecule piperine was investigated for the antibiofilm and antihyphal activities against C. albicans. Piperine demonstrated a concentration dependent antibiofilm activity without exerting negative impact on growth and metabolic activity. Inhibition in the hyphal development was witnessed through confocal laser scanning microscopy and scanning electron microscopy. Interestingly, piperine displayed a tremendous potential to inhibit the virulence associated colony morphologies such as filamentation and wrinkling. Furthermore, piperine regulated morphological transitions between yeast and hyphal forms by inhibiting hyphal extension and swapping hyphal phase to yeast forms yet under filamentation inducing circumstances. Remarkably, piperine challenged C. albicans exhibited low potential for spontaneous antibiofilm resistance development. In addition, piperine effectively reduced in vivo colonization and prolonged survival of C. albicans infected Caenorhabditis elegans, thereby expounding the distinct antivirulent potential. Transcriptomic analysis revealed piperine significantly downregulating the expression of several biofilm related and hyphal-specific genes (ALS3, HWP1, EFG1, CPH1 etc.). Furthermore, no acute toxicity was observed in the HBECs and nematodes exposed to piperine. Altogether, results from this study reveals the potential of piperine to inhibit biofilm and hyphal morphogenesis and its in vivo efficacy, innocuous nature to HBECs suggests that piperine may be considered as a potential candidate for the treatment of biofilm associated C. albicans infection, especially for oral candidiasis.